Uniform-saturation modification for hydrophilicity improvement of large-scale PET by plasma-electrified treatment. (5th December 2022) - Zhu, Xi; Li, Fangsong; Guan, Xiuhan; Xu, Jingang; Cui, Xinglei; Huang, Jialiang; Liu, Feng; Fang, Zhi
Graphical abstract: Highlights: DBD plasma treatment applied to the surface modification of large-scale polymer PET with high efficiency and no pollution product. New structure of air DBD plasma for large-scale polymer treatment. Optimized plasma treatment by DBD electrode design and processing regulation. Molecular simulation revealing the saturation of the hydrophilicity modification for polymer surface. Abstract: Low surface energy and poor hydrophilicity of the polymer film reduces its working stability and service life in various application fields, but the industrial surface modification for the large-scale film requires the dynamic and efficient processing techniques with the uniform treatment effects. In this study, an efficient air dielectric barrier discharge (DBD) tube electrode array for large-scale polyethylene glycol terephthalate (PET) film treatment was established, and its discharge characteristics and treatment effects were further investigated by experiment and simulation at a microscopic scale. It shows that the increase in the number of electrodes and the applied voltage leads to diffuse and uniform discharge with strong luminous intensity, where the emission spectra is dominated by the second positive band of nitrogen molecules. Moreover, the increase in applied voltage and the decrease in treatment speed both enhance the surface hydrophilicity and the modification uniformity, which is caused by the rough surface and the introduction of oxygen-containing groups by the air DBD treatment. Combined with quantum chemistry calculations, it is speculated that the further modification reaches saturation with particles (COOH group) that causes hydrophilicity. It reveals that the introduction of OH groups on PET surface accounts for the increase in the molecular dipole moment and hydrophilicity; by contrast, the COOH group issued from the further oxidation of OH group decreases the molecular polarity, thereby causing the saturation of particles which causes the hydrophilicity by the air DBD treatment.